Evidence-based teaching: effective teaching practices in primary school classrooms (UCL Press, 2024)
Understanding and measuring effective teaching practices in low- and middle-income countries is a complex process that requires a contextualised knowledge of teaching quality, as well as adaptable instruments that can reliably capture teachers' varied classroom behaviours. One approach developed with these purposes in mind is Teach Primary, a classroom observation framework designed and revised in 2021 by the World Bank. This framework captures the time teachers spend on learning and the quality of teaching practices which help to enhance pupils' cognitive and socio-emotional skills, as well as aspects of the physical environment which may influence teaching quality. Using the Teach Primary framework, this article examines evidence regarding effective instructional practices in primary school classrooms, with highlighted examples from low- and middle-income countries. It also sheds light on the criticality of instrument contextualisation, given variations in how practices can be valued and implemented in different settings and how structural quality factors can influence teachers' use of strategies. Challenges and limitations relating to the use of the Teach Primary framework are discussed, along with implications for teacher education and evaluation.